2013
DOI: 10.5812/ircmj.2384
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiosis: Risk Factors, Clinical Characteristics and Outcome

Abstract: Nocardiosis has been reported increasingly in recent two decades, probably due to improvement in isolation of the organism and increased burden of immune compromised patients. Nocardia occasionally has been reported in healthy people. A case series of definitive Nocardiosis (2002 to 2010), clinical characteristics, underlying diseases, immune status and in-patient outcome were studied in a tertiary referral center. Twenty one patients with definite diagnosis of Nocardiosis were studied. 17 cases (81%) had an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…15 In an observational study of all the patients diagnosed with pulmonary Nocardiosis over a 13-year period the predisposing conditions were defined as; COPD (23%) transplantation(29%), HIV infection (19%), alcoholism (6.5%) and treatment with steroids (64.5%). 16 Early identification and therapy of Nocardiosis is important for mortality especially among immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 In an observational study of all the patients diagnosed with pulmonary Nocardiosis over a 13-year period the predisposing conditions were defined as; COPD (23%) transplantation(29%), HIV infection (19%), alcoholism (6.5%) and treatment with steroids (64.5%). 16 Early identification and therapy of Nocardiosis is important for mortality especially among immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a diagnostic biopsy should always be performed in order to make smear microscopy and culture, which in our case showed the bacteria Nocardia asteroides . [ 3 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…This decrease may be the result of an incomplete differentiation in macrophages, which increases susceptibility to infections such as nocardial infections. [ 7 8 ] Among the numerous suggested etiologies for PAP, such as lung infections and hematologic malignancies, studies have shown a correlation between PAP and a chronic exposure to silica dust. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests there are defined risk factors for Nocardia species infection: HIV infection [ 5 ], corticosteroid therapy or use of immunosuppressive agents [ 5 ],[ 6 ], organ transplantation [ 6 ], and diabetes mellitus [ 3 ]. Preexisting rheumatic disease treated with immunosuppressant therapy, as in Case 1, is another risk factor for Nocardia species infection [ 14 ].…”
Section: Case Presentationmentioning
confidence: 99%